2022
DOI: 10.1186/s12909-022-03535-z
|View full text |Cite
|
Sign up to set email alerts
|

Do learning style preferences influence the cumulative gross point average and self directed learning hours in dental students: a preliminary study

Abstract: Background Learning styles influence the outcome of the student performances based on preliminary data available. To evaluate whether the learning styles discriminate the cumulative gross point average (CGPA) scores and self-directed learning hours (SDL) in an integrated curriculum of dental students. Methods Participants in this blinded cross-sectional study were dental students enrolled in the Bachelor of Dental & Oral Surgery program at XXXX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While The use of technology made it easier for students to access educational material and communicate with their peers to solve group assignments, it also provided the possibility of communicating with the teacher at any time [ 62 ], as the material was designed to suit the distance learning environment. It includes accessing various learning activities that adapt to student's learning styles and what best suits them in using learning resources, which improve skills in management and decision-making [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…While The use of technology made it easier for students to access educational material and communicate with their peers to solve group assignments, it also provided the possibility of communicating with the teacher at any time [ 62 ], as the material was designed to suit the distance learning environment. It includes accessing various learning activities that adapt to student's learning styles and what best suits them in using learning resources, which improve skills in management and decision-making [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic treatment is necessary for a sizable part of dental emergencies treated globally, and there is a growing demand to train and educate dental students in this skill so they would be more ready to carry out such treatment with satisfactory outcomes [ 1 , 2 ]. However, numerous investigations have shown that general dentists do not deliver endodontic care of a high standard [ 3 – 4 ].…”
Section: Introductionmentioning
confidence: 99%